MicroRNA-382 inhibits cell growth and migration in colorectal cancer by targeting SP1 - Ren, Yupeng (Biol Res, 2018)
BACKGROUND: Emerging evidence showed that microRNAs (miRs) play critical roles in human cancers by functioning as either tumor suppressor or oncogene. MIR-382 was found to function as tumor suppressor in certain cancers. However, the role of MIR-382 in colorectal cancer (CRC) is largely unknown. Specificity protein 1 (SP1) is highly expressed in several cancers including CRC and is correlated with poor prognosis, but it is unclear whether or not MIR-382 can regulate the expression of SP1. METHODS: MIR-382 expression level was measured by reverse transcription-quantitative polymerase chain reaction. The connection between MIR-382 and SP1 was validated by luciferase activity reporter assay and western blot assay. Cell counting kit-8 assay and wound-healing assay were conducted to investigate the biological functions of MIR-382 in CRC. RESULTS: In this study, we found MIR-382 expression was downregulated in CRC tissues and cell lines, and the transfection of MIR-382 mimic decreased cell growth and migration. Furthermore, we identified SP1 was a direct target of MIR-382. Overexpression of MIR-382 decreased the expression of SP1, whereas MIR-382 knockdown promoted SP1 expression. We also observed an inversely correlation between MIR-382 and SP1 in CRC tissues. Additionally, we showed that knockdown of SP1 inhibited cell growth and migration and attenuated the effect of MIR-382 inhibitor on cell behaviors. CONCLUSIONS: In conclusion, the present study describes a potential mechanism underlying a MIR-382/SP1 link contributing to CRC development. Thus, MIR-382 may be able to be developed as a novel treatment target for CRC.